Relationship between severity of periodontitis and masseter muscle activity during waking and sleeping hours - Kato, Seiya; Ekuni, Daisuke; Kawakami, Shigehisa; Mude, Acing Habibie; Morita, Manabu; Minagi, Shogo (Archives of oral biology, 2018)
•Subjects with periodontitis showed much masseter muscle activity.•Masseter muscle activity would be highly related to periodontal tissue destruction.•The phasic and mixed episodes were found to be long in subjects with periodontitis. This study was conducted to investigate whether the masseter muscle activity shows any specific pattern in relation to the severity of periodontitis. Sixteen subjects with no or mild periodontitis (NMP group) and 15 subjects with moderate or severe periodontitis (MSP group) were enrolled. Plasma IgG antibody titer was examined using Porphyromonas gingivalis as a bacterial antigen. Surface electromyography (EMG) of the masseter muscles was continuously recorded using an ambulatory surface EMG recording device while patients were awake and asleep. Masseter muscle activity was analyzed using intensities of 5%–10% maximal voluntary clenching (MVC), 10%–20% MVC, and >20% MVC. Furthermore, EMG levels of 20% MVC were adopted as the threshold for analysis of phasic, tonic, and mixed EMG activities. The cumulative duration of masseter muscle activity and bruxism episodes was calculated as duration per hour. There was no significant difference in plasma IgG antibody titers against P. gingivalis between the NMP and MSP groups (p = 0.423). During waking hours, the duration of masseter muscle activity with an intensity of >20% MVC was significantly longer in the MSP group than in the NMP group (p = 0.037). During sleeping hours, the duration of masseter muscle activity at all MVC intensities was significantly longer in the MSP group than in the NMP group (all p < 0.05). Additionally, the duration of phasic and mixed episodes was significantly longer in the MSP group than those in the NMP group while both awake and asleep (all p < 0.05). The results of this study suggested that masseter muscle activity might be related to the severity of periodontitis.